AKALAZYALI HASTALARDA KLİNİK, RADYOLOJİK VE MANOMETRİK BULGULAR ARASINDAKİ İLİŞKİLER - DOBRUCALI, Ahmet; ÇURGUNLU, Aslı; ÇELİK, A. Ferhat and İLKOVA, Feryal and TUNCER, M. Murat and BAL, Kadir and UZUNİSMAİL, Hülya and; AKUL, İbrahim and OKTAY, Ergun (Cerrahpaşa Medical Journal, 2014)
Background and Design. Achalasia is a well known primary motor disorder of the esophagus in which the lower esophageal sphincter (LES) exerts abnormally high resting pressure and incomplete relaxation with swallowing. Dynamic investigations, mainly esophageal manometry and radiological examination are needed for the diagnosis and followup after treatment. We present the clinical manifestations, radiological manometric abnormalities of 26 patients with achalasia seen between 1993 and 1997. Results. Dysphagia was significantly correlated with bird beak deformity and impaired emptying on esophagogram. No significant relationship was found between the LES pressure and clinical and radiological features. Nonperistaltic wave amplitude and LES relaxation were inversely and significantly correlated with impaired emptying on esophagogram. Conclusion. Radiological findings of achalasia may not be due to hypertensive LES but decreased lower sphincter relaxation may be responsible for dysphagia and impaired esophageal emptying. Also LES pressure is in normal range in 35% of patients with achalasia. Achalasia and hiatal hernia may coexist in 8% of the patients.